The Yeast and Hypha Phases of Candida krusei Induce the Apoptosis of Bovine Mammary Epithelial Cells via Distinct Signaling Pathways - Yuhang Miao; Tao Ding; Yang Liu; Xuezhang Zhou; Jun Du (Animals, 2023)
Infection with Candida spp. is a significant cause of bovine mastitis globally. We previously found that C. krusei was the main pathogen causing mycotic mastitis in dairy cows in Yinchuan, Ningxia, China. However, whether the infection of this pathogen could induce apoptosis in BMECs remained unclear. In this report, we explored the apoptosis and underlying mechanism of BMECs induced by C. krusei yeast and hypha phases using a pathogen/host cell co-culture model. Our results revealed that both the yeast and hypha phases of C. krusei could induce BMEC apoptosis; however, the yeast phase induced more cell apoptosis than the hypha phase, as assessed via electronic microscopy and flow cytometry assays. This finding was further corroborated via the measurement of the mitochondrial membrane potential (MMP) and the TUNEL test. Infection by both the yeast and hypha phases of C. krusei greatly induced the expression of proteins associated with cell death pathways and important components of toll-like receptor (TLR) signaling, including TLR2 and TLR4 receptors, as determined via a Western blotting assay. BMECs mainly underwent apoptosis after infection by the C. krusei yeast phase through a mitochondrial pathway. Meanwhile, BMEC apoptosis induced by the C. krusei hypha phase was regulated by a death ligand/receptor pathway. In addition, C. krusei-induced BMEC apoptosis was regulated by both the TLR2/ERK and JNK/ERK signaling pathways. These data suggest that the yeast phase and hypha phase of C. krusei induce BMEC apoptosis through distinct cell signaling pathways. This study represents a unique perspective on the molecular processes underlying BMEC apoptosis in response to C. krusei infection.